Development Of Steer-By-Wire (SBW) Controller System For Steering Respone - Amir, Mohd Zubir (2016)
This research focuses on the development of Steer-By-Wire (SBW) controller system for steering response. The steering system is an essential part of the interface between the driver and the vehicle that provides the possibility of lateral guidance. SBW system is means as removing the mechanical linkages and hydraulic part with electronic system. The development of vehicle model consists of ride, tire and handling models used in this study. The vehicle model is then validated with CarSimEd. The relation between the rack and pinion is identified for the steering ratio on SBW model. The steering system is modeled combine with actuator model in MATLAB Simulink. There are several types of controller are used on SBW system to find the similar response with the conventional steering. The selected controller will be applied on SBW system to control the actuator in simulation and experimental. The simulation result is validated with Hardware-in-the-Loop Simulation (HiLS) in real time situation using xPC Target application in MATLAB Simulink to control SBW system in experiment. The target outcome of this study for SBW steering system is to get a responsiveness similarity to conventional steering system with selected controller by comparing both steering system. The study shows that such similarity was achieved. The study of SBW system response is beneficial in the SBW system with the proposed controller can be implemented on real vehicles.